Potential of MSCA1 for isolating osteogenic cells in a chondrocyte population - Ausra Unguryte; Ilona Uzieliene; Edvardas Bagdonas; Aiste Zentelyte; Narūnas Porvaneckas; Eiva Bernotiene (Scientific Reports)
Abstract The aim of the present study was to elucidate the utility of Mesenchymal Stem Cell Antigen-1 (MSCA1) (tissue nonspecific alkaline phosphatase (TNAP)) as a potential marker for purification of human chondrocyte fraction with less heterogenous phenotype from those with osteogenic properties. Chondrocytes were isolated from human osteoarthritis cartilage and sorted according to MSCA1 expression by MACS (Magnetic-activated cell sorting) and FACS (Fluorescence-activated cell sorting) techniques (MSCA1high and MSCA1low), analyzed for gene expression, osteogenic and adipogenic differentiation capacities, and were compared between the sorted populations. Gene expression analyses revealed upregulation in osteogenic genes (ALPL and RUNX2) and significantly lower expression of chondrocyte-specific genes (COL2A1, SOX9 and MIA) in sorted MSCA1high, as compared to MSCA1low. Expression of Aldehyde dehydrogenase isoform gene ALDH1A2 was enriched in MSCA1low chondrocytes. Stronger osteogenic differentiation was observed in MSCA1high, as compared to the unsorted cells, and particularly, MSCA1low chondrocytes. Expression of MSCA1 in human chondrocytes is biased in their commitment to the osteogenic lineage. We demonstrate that MSCA1 can be used as a marker for separation of cells, prone to differentiate towards osteogenic lineage from those, retaining chondrogenic phenotype. This may allow enrichment of a chondrogenic population and separation from undesirable osteoprogenitors.